The spectrum of clinical presentation in haploinsufficiency of A20; a case report of a novel mutation in TNFAIP3 gene - Debeljak, M.; Blazina, S.; Brecelj, J.; Avčin, T.; Toplak, N. (Frontiers in Pediatrics, 2023)
Haploinsufficiency of A20 was first described in 2016 as a new autoinflammatory disease that clinically presents as early onset Behcet’s disease. After first publication of 16 cases, other patients were found, and the spectrum of clinical presentation has expanded. In this short report we will present a patient with novel mutation in TNFAIP3 gene. Clinical presentation was not very typical for Haploinsufficiency A20, but he had presentation of an autoinflammatory disease with recurrent fever, abdominal pain, diarrhoea, respiratory tract infections and elevated parameters of inflammation. We will emphasise the importance of genetic testing, especially in cases that are clinically not typical for a single autoinflammatory disease.